Legalization of Regional Regulation on Domestic Workers in Special Region of Yogyakarta and its Challenge - Sargini, NFN; Jumiyem, NFN; Muryanti, NFN (Yayasan Jurnal Perempuan, 2017)
This paper examines the legislation process of Proposed Regional Regulation on Domestic Workers (Raperda PRT) in DIY. The regional regulation becomes important because domestic workers have a significant role for working family and for those who are busy with public life. This resulted in an incresed demand for this proffesion every year. Unfortunately, the absence of governing regulation for this profession lead to the use of a very unclear and messy working relationship practice by the DW (PRT)and the customer (service user). The violation of employment relationship becomes regular occurance, as well as the violence experienced by domestic workers, whether physical, psychological, economic, sexual or social. In Yogyakarta, the Domestic Workers Protection Network (JPPRT) of DIY has suggested that the various type of violence experienced by domestic workers can not be separated from the absence of regulationthat governing the working relation of domestic workers and service user. Against this background JPPRT decided to pioneer and propose a draft for regional regulation for domestic workers in The Special Region of Yogyakarta (DIY).